Light-dark dependent changes in chloroplast and mitochondrial activity in Chlamydomonas reinhardtii - Dhawan, Gunjan; Rao, Basuthkar Jagadeeshwar (Frontiers in Plant Science, 2025)
In photosynthetic organisms, the inter-organellar coordination between photosynthetic and respiratory processes is fundamental for maintaining cellular energy homeostasis. These organelles not only operate distinct bioenergetic pathways but also engage in extensive metabolic cross-talk to balance energy production, redox status and metabolic demands, especially under fluctuating light-dark conditions. Such coordination has been widely appreciated across plant and algal systems but it remains relatively less explored, particularly in synchronous cultures where cellular rhythms can be more precisely examined. Our study investigated the coordination in photosynthetic and mitochondrial activity during (12:12 h) light-dark cycle using synchronized Chlamydomonas reinhardtii cultures. Live cell confocal imaging revealed light-dark-dependent mitochondrial morphology transitions from fragmented to intermediate to tubular forms by the end of 12 hr of light period, which reverses sharply through 6 and 12 hr of dark. Concurrently, chloroplast show novel transitions from an intact cup (light) to a distorted and punctured structure (dark), which gets reversed in light phase. Spatial mapping showed tubular mitochondria positioned peripherally to the chloroplast cup in light, whereas fragmented and intermediate mitochondria were diffused around distorted chloroplast in dark, which again gets reversed in light. Functional analysis using 77K spectroscopy and photosynthetic protein levels (PsaA and D1) reflected that PSI/PSII fluorescence ratio remains stable in continuous light condition but increased exceptionally in continuous dark, which led to transient changes observed in fluorescence ratio in light/dark-dependent manner in synchronous cultures. Mitochondrial activity, measured using Seahorse flux analyzer, showed basal oxygen consumption rate in continuous light and a marked reduction in continuous dark condition, resulting in dynamic changes observed in light-dark cycle, indicating a coordination in the organellar function. Further, Target of rapamycin (TOR) kinase activity was essential to maintain inter-organellar coupling as evidenced by subdued fluctuations following TOR kinase inhibition. The study, for the first time, argues for (12:12 h) light-dark cycle-mediated coupled dynamics between mitochondria and chloroplast in C. reinhardtii, offering new insights into the temporal regulation of cellular energy dynamics.